2010
DOI: 10.1007/s11920-010-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Hypomania and Mania: Differential Neurochemical, Neuropsychological, and Pharmacologic Triggers and Their Mechanisms

Abstract: Current data suggest that monoamines, acetylcholine, amino acids, cortisol, thyroid hormones, and melatonin may be involved in the pathophysiology of bipolar disorder (BPD). Any neuropsychological or pharmacologic factor causing a disturbance in these neurochemicals may trigger manic/hypomanic switching. Antidepressants, stimulants, anticholinergics, steroids, and thyroid hormone have been reported to cause treatment-emergent mania (TEM) in BPD, but only recently have the traditional antidepressants been syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
(60 reference statements)
0
9
0
1
Order By: Relevance
“…These groups of patients are more likely to have TEM than those without these characteristics [38,39] . At the present time, using antidepressants in bipolar depression should follow the recommendations of the International Society for Bipolar Disorders task force report on antidepressant use in bipolar disorders [40] .…”
Section: Discussionmentioning
confidence: 99%
“…These groups of patients are more likely to have TEM than those without these characteristics [38,39] . At the present time, using antidepressants in bipolar depression should follow the recommendations of the International Society for Bipolar Disorders task force report on antidepressant use in bipolar disorders [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Stimulants by themselves will only worsen mood stability in PBD (see [160] for a review). Recent pharmacological fMRI studies in PBD showed improvement in inhibitory function and mood stability with lamotrigine, divalproex and risperidone [68,161164].…”
Section: Neurobiologically-informed Treatments Of Cognitive and Emotionmentioning
confidence: 99%
“…These changes may affect sleep-wake rhythms (because of occupation and leisure), 7 use of stimulants, 8 a shift away from the Mediterranean diet, 9 and introduction of strong liquors in place of wine and beer 10 (light beer is a traditional drink in Sardinia), all factors that may foster emergence of hypo/manic episodes in predisposed and vulnerable youths. Young men coming from traditional communities are thought to be particularly vulnerable to this type of stress because they are exposed to high levels of competition.…”
Section: Introductionmentioning
confidence: 99%